Innovative development of college library services to enhance user experience - Teguh Yudi Cahyono (AL Maktabah, 2024)
This research explores the impact of innovative developments in higher education library services on user experience. The main focus of the research was to assess how the implementation of the latest technologies, such as digital libraries and RFID systems, as well as the design of library spaces affect the satisfaction and effectiveness of services for users. Through a descriptive qualitative approach, data was collected through in-depth interviews, participatory observation, and document analysis. Findings show that innovations such as access to digital resources and a more efficient borrowing system have significantly improved user satisfaction. The research also identified challenges, such as lack of training for new technologies and concerns regarding data privacy, which affected the acceptance of innovative services. Designing spaces that are comfortable and supportive of the learning process proved important in improving the user experience, although there is still a need for further customization. The implications of this study suggest that higher education libraries need to balance the implementation of technology with the provision of adequate support and ensure clear privacy policies to meet the needs of all users. This research provides valuable insights for the development of innovative strategies in library services to improve effectiveness and user satisfaction in the digital era.